SARS-CoV-2 Spike has broad tropism for mammalian ACE2 proteins yet exhibits a distinct pattern of receptor usage when compared to other β-coronavirus Spike proteins. Issue 5 (27th May 2022) - Conceicao*, Carina; Thakur*, Nazia; Human, Stacey; Kelly, James T; Logan, Leanne; Bialy, Dagmara; Bhat, Sushant; Stevenson-Leggett, Phoebe; Zagrajek, Adrian K; Hollinghurst, Philippa; Varga, Michal; Tsirigoti, Christina; et al.
Abstract : The Coronavirus Disease 2019 (COVID-19) pandemic, caused by SARS Coronavirus 2 (SARS-CoV-2), continues to cause significant mortality in human populations worldwide. SARS-CoV-2 has high sequence similarity to SARS-CoV and other related coronaviruses circulating in bats. It is still unclear whether transmission occurred directly from bats to humans, or through an intermediate host, bringing into question the broader host range of SARS-CoV-2. Using a combination of low biocontainment entry assays as well as live virus, we explored the receptor usage of SARS-CoV-2 using angiotensin-converting enzyme 2 (ACE2) receptors from 22 different species. We demonstrated that in addition to human ACE2, the Spike of SARS-CoV-2 has broad tropism for other mammalian ACE2s, including dog, cat and cattle. However, comparison of SARS-CoV-2 receptor usage to the related SARS-CoV and bat coronavirus, RaTG13, identified distinct patterns of receptor usage, with the two human viruses being more closely aligned. Finally, using bioinformatics, structure analysis and targeted mutagenesis, we identified key residues at the Spike-ACE2 interface which may have played a pivotal role in the emergence of SARS-CoV-2 in humans, some of which are also mutated in newly circulating variants of the virus. To summarise, the broad tropism of SARS-CoV-2 at the point of viral entry identifies the potential risk of infection of a wide range of companion animals, livestock and wildlife.